A prospective, randomized, controlled trial comparing two doses of oestrogen therapy after hysteroscopic adhesiolysis to prevent intrauterine adhesion recurrence. Issue 5 (November 2017) - Guo, Jun; Li, TC; Liu, YuHuan; Xia, EnLan; Xiao, Yu; Zhou, FengQiong; Yang, Xue
Abstract: The aim of this prospective, randomized, controlled trial was to evaluate the efficacy of different doses of oestrogen treatment (2 mg and 6 mg daily) after hysteroscopic adhesiolysis in patients with moderate to severe adhesion according to the American Fertility Society (AFS) classification of intrauterine adhesions. A total of 121 patients were included in the final analysis. Fifty-nine patients received 2 mg oestrogen daily (low-dose group), and 62 received 6 mg oestrogen daily (high-dose group) for three cycles after surgery. Second- and third-look outpatient hysteroscopy was performed 4 and 8 weeks after the initial surgery. There was no difference in the menstrual pattern and AFS scores before and after surgery between the two groups, and AFS scores at the second- and third-look hysteroscopy were found to be significantly lower than the scores before surgery in both groups (both P < 0.01). While this study did not address the fundamental question of whether oestrogen adjuvant therapy prevents the recurrence of intrauterine adhesions, the findings do not support the use of high-dose oestrogen therapy after hysteroscopic adhesiolysis.